HIGHER EDUCATION INSTITUTIONS IN THE SPACE OF INDICATORS OF THE INTERNATIONAL RATINGS - Dmitry A. Rubvalter; Yury S. Bogachyov; Valery P. Shestak (Высшее образование в России)
The article gives an assessment of innovative development of Russia on the basis of studying of the«lost» international ratings. «The space of indicators», formed by partial indicators of innovative development used in the international ratings such as possibilities of the country to generate, use and extend knowledge, the potential of economy of knowledge, educational and personnel resources, etc. The similar space can define priorities for activity of the state institutions of development – economy, education, science, business. There is offered a model image of «the space of indicators» in the form of the petal chart, which integrates families of orgraphs – each orgraph represents a certain sphere of activity, partial indicators or estimates of activity are represented as top, or knots of the orgraph, and communication between as arches, or edges of the orgraph. All orgraphs meet into the uniform center where the integrated index of innovative development is maximum and equal 100%. This model received the name «convergent model of indicative planning» – CMIР; the modelallows to choose priorities for concentration and the most effective use of resources of higher education institution that is necessary for active participation of higher education institutions in innovative development of Russia.